Optimasi Basis Sabun Padat Transparan Menggunakan Minyak Zaitun dan Pengaruh Konsentrasi Sukrosa Terhadap Transparansi Sabun: Optimization of Transparent Solid Soap Base Using Olive Oil and the Effect of Sucrose Concentration on Soap Transparency - Risma Dwi Novianti; Wisnu Cahyo Prabowo; Angga Cipta Narsa (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Transparent solid soap has a luxurious, classy, and attractive appearance so it is often sold as a souvenir which is relatively expensive but still has a unique and exclusive appearance. In the process of making transparent soap, sugar (sucrose) functions to form transparency on the soap. Olive oil is one of the potential raw materials for soap making because it has a high content of oleic acid which is good for skin health. This study aims to formulate a transparent solid soap based on raw materials of olive oil and lintut leaf essential oil that meets the characteristics of transparent solid soap and soap quality requirements in accordance with SNI (1994). Sucrose as a transparent agent for soap is concentrated into 14%, 18%, and 22%. Then the base optimization was carried out by varying olive oil and 30% NaOH in three formulations. The results showed that the sucrose concentration was 22% which resulted in the most transparent preparation. Then the evaluation of base optimization shows that all formulas have good characteristics and only formula 2 (18% olive oil and 12% NaOH) fulfills all the soap quality requirements according to SNI (1994).